Dust entrainment in magnetically and thermally driven disk winds - Rodenkirch, Peter; Dullemond, Cornelis (Astronomy and astrophysics, 2022)
Magnetically and thermally driven disk winds have gained popularity in the light of the current paradigm of low viscosities in protoplanetary disks that nevertheless present large accretion rates even in the presence of inner cavities. The possibility of dust entrainment in these winds may explain recent scattered light observations and constitutes a way of dust transport towards outer regions of the disk.Aims. We aim to study the dust dynamics in these winds and explore the differences between photoevaporation and magnetically driven disk winds in this regard. We quantify maximum entrainable grain sizes, the flow angle, and the general detectability of such dusty winds.Methods. We used the FARGO3D code to perform global, 2.5D axisymmetric, nonideal MHD simulations including ohmic and ambipolar diffusion. Dust was treated as a pressureless fluid. Synthetic observations were created with the radiative transfer code RADMC-3D.Results. We find a significant difference in the dust entrainment efficiency of warm, ionized winds such as photoevaporation and magnetic winds including X-ray and extreme ultraviolet heating compared to cold magnetic winds. The maximum entrainable grain size varies from 3 μm−6 μm for ionized winds to 1 μm for cold magnetic winds. The dust flow angle decreases rapidly with increasing grain size. Dust grains in cold magnetic winds tend to flow along a shallower angle compared to the warm, ionized winds. With increasing distance to the central star, the dust entrainment efficiency decreases. Larger values of the turbulent viscosity increase the maximum grain size radius of possible dust entrainment. Our simulations indicate that diminishing dust content in the outer regions of the wind can be mainly attributed to the dust settling in the disk. The Stokes number along the wind launching front stays constant in the outer region. In the synthetic images, the dusty wind appears as a faint, conical emission region which is brighter for a cold magnetic wind.